Comprehensive Application of Autologous Costal Cartilage Grafts in Rhino- and Mentoplasty. Issue 7 (October 2019) - Zhang, Lu; Ma, Wen-Shu; Bai, Ji-Ping; Li, Xing-Xing; Li, Hong-Dong; Zhu, Tao; Sun, Jian-Yu; Ge, Hong-Gang; Pang, Yun; Xue, Feng; Cheng, Li-Ying; Jin, Rong; et al.
Abstract : Background: Underdevelopment of nose and chin in East Asians is quite common. Rhinoplasty and mentoplasty are effective procedures to solve the above-depicted defects and can achieve remarkable cosmetic effects. An autologous costal cartilage graft has become an ideal material for rhinoplasty, especially for revision surgery. However, many problems in the clinical application of costal cartilage remain unresolved. This study is to investigate application strategies of autologous costal cartilage grafts in rhino- and mentoplasty. Methods: The methods involved are as follows: application of an integrated cartilage scaffold; comprehensive application of diced cartilage; and chin augmentation of an autologous costal cartilage graft. Results: In this study, satisfactory facial contour appearance was immediately achieved in 28 patients after surgery; 21 patients had satisfactory appearance of the nose and chin during the 6- to 18-month follow-up. Cartilage resorption was not observed. Two patients had nasal tip skin redness and were cured after treatment. Conclusion: This procedure can be used to effectively solve: curvature of the costal cartilage segment itself; warping of the carved costal cartilage; and effective use of the costal cartilage segment. The procedure has achieved satisfactory outcomes, and its application is worth extending to clinical practice.